Carbon Accumulation and Partitioning in Sub-Humid Forest Stands of West Bengal India - Shukla, Gopal; Pala, Nazir A.; Moonis, Mohammad; Chakravarty, Sumit (Indian Forester, 2018)
The present study was conducted at Chilapatta Reserve Forest under Cooch Behar Wildlife Division in Terai zone of West Bengal. The study was aimed to analyze the carbon stock and its accumulation in different components of various floristic layers including trees, herbs and shrubs based on dominant species/stands. The dominant stands selected were Lagerstroemia parviflora, Shorea robusta, Tectona grandis and Michelia champaca. Aboveground biomass and carbon accumulation was estimated for all these stands. The majority of the contribution to biomass and carbon of the different stands was contributed by the trees (99 %) while a negligible amount was contributed by shrubs (0.25 %) and herbs (0.06 %). Stems were the dominant contributor toward biomass accumulation followed by branches, roots, leaves and foliage in the trees.